2000
DOI: 10.1037/0022-3514.78.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Framing interethnic ideology: Effects of multicultural and color-blind perspectives on judgments of groups and individuals.

Abstract: In 3 experiments, White American college students received a message advocating either a color-blind or a multicultural ideological approach to improving interethnic relations and then made judgments about various ethnic groups and individuals. Relative to a color-blind perspective, the multicultural perspective led to sU'onger stereotypes, greater accuracy in these stereotypes, and greater use of category information in judgments of individuals. This increase in between-category differentiation occurrexi both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
544
3
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(595 citation statements)
references
References 80 publications
23
544
3
9
Order By: Relevance
“…More specifically, the other major contribution of the present research is in showing that not all cultural worldviews are equally impactful in a given setting. The rationale behind our propositions in this regard comes from an analysis of 15 years of research using the experimental paradigm developed by Wolsko, Park, Judd, andWittenbrink (2000, see Sasaki &Vorauer, 2013 for a review). Wolsko et al (2000) were the first to suggest that one could study the effect of broad cultural ideologies on cognition and behaviors in the laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the other major contribution of the present research is in showing that not all cultural worldviews are equally impactful in a given setting. The rationale behind our propositions in this regard comes from an analysis of 15 years of research using the experimental paradigm developed by Wolsko, Park, Judd, andWittenbrink (2000, see Sasaki &Vorauer, 2013 for a review). Wolsko et al (2000) were the first to suggest that one could study the effect of broad cultural ideologies on cognition and behaviors in the laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind our propositions in this regard comes from an analysis of 15 years of research using the experimental paradigm developed by Wolsko, Park, Judd, andWittenbrink (2000, see Sasaki &Vorauer, 2013 for a review). Wolsko et al (2000) were the first to suggest that one could study the effect of broad cultural ideologies on cognition and behaviors in the laboratory setting. In their paradigm, participants are randomly allocated to a condition stressing the value of multiculturalism or colorblindness in the management of intergroup relations.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the Netherlands, Verkuyten (2005) found that the more Dutch participants endorsed the idea of multicultural recognition, the more likely they were to evaluate the Muslim Turkish out-group positively. Some experimental studies have further shown a causal positive effect of multiculturalism on automatic and explicit forms of racial attitudes (e.g., Richeson & Nussbaum, 2004;Wolsko, Park, Judd, & Wittenbrink, 2000). Furthermore, in the context of New Zealand, Ward and Masgoret (2006) found that the endorsement of multicultural recognition was associated with decreased perceptions of group threat, which in turn led to more positive attitudes toward immigrants.…”
Section: Multiculturalismmentioning
confidence: 99%
“…Individuals who endorse multiculturalism appear to feel less threatened by minority groups and multicultural ideology involves the acceptance of diversity and equal opportunities. Multiculturalism can provide and promote positive evaluative contexts (Hogan & Mallott, 2005;Wolsko et al, 2000). However, multicultural interventions should be sensitive to the danger that they can lead to reified and essentialist group distinctions that promote group stereotyping and that endangers social unity and cohesion in particular settings (e.g., Verkuyten, 2006;Vogt, 1997).…”
Section: Political Tolerance and Prejudicementioning
confidence: 99%
“…Discriminatory) design. Each questionnaire contained a measure of ingroup identification, the manipulation of ingroup norm and intergroup similarity, and a representativeness estimate task (see below; see also Wolsko, Park, Judd & Wittenbrink, 2000). The questionnaire also contained manipulation-checking questions.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%